Sulfonation of Eugenol-Diallyl Phthalate Copolymer as Base Material of Supercapacitor Electrode Material - Ngadiwiyana Ngadiwiyana; Cinta Nur Nabila; Ismiyarto Ismiyarto; Marcelinus Christwardana (Jurnal Kimia Sains dan Aplikasi, 2024)
Polyeugenol is a polymer synthesized from renewable natural resources and has potential as a supercapacitor electrode material. Polyeugenol was modified by the addition of diallyl phthalate to increase structural density and thermal stability and the addition of sulfonate groups to increase ion exchange capacity and electrical conductivity. This research begins with the synthesis of eugenol-diallyl phthalate copolymer (PEGDAF) carried out by cationic polymerization using BF3O(C2H5)2 catalyst and sulfonation of eugenol-diallyl phthalate copolymer (SPEGDAF) using sulfuric acid. The synthesis of PEGDAF in the form of pink solids with a yield of 68.44%, a molecular weight of 6739.99 Daltons, and a melting point of 85°C, FTIR analysis showed that the formation of PEGDAF was characterized by the loss of vinyl groups with the absence of C=C alkene wavenumber absorption which is the wavenumber absorption of eugenol and diallyl phthalate, respectively 1640 cm-1 and 1647 cm-1 and TGA with a mass loss of 5% and 10% at 176°C and 219°C. SPEGDAF results in dark purple solids with a sulfonation degree of 17.18% and a cation exchange capacity of 0.4186 meq/g, molecular weight 8342.25 Daltons, melting point 114°C. Analysis using FTIR showed the presence of sulfonate groups with the resulting absorption peaks of 1218 cm-1 (S=O), 1065 cm-1 (S-O), and 578 cm-1 (C-S) and TGA with a mass decrease of 5% and 10% at temperatures of 169°C and 215°C. Potential test of supercapacitor electrode material with Cyclic Voltammetry and Electrochemical Impedance Spectroscopy obtained a specific capacitance value of 3.23 × 10-3 F/g and ion conductivity of 7.58 × 10-6 S/cm.